Levantamento soro-epidemiológico de artrite-encefalite caprina em rebanhos caprinos no semiárido Baiano. - LIMA, C. C. V. de (2011)
Seroepidemiological survey of caprine arthritis encephalitis in goat flocks of semi-arid region in Bahia State, Brazil. Abstract - In order to determine the serological prevalence of CAE in the Microregion of Juazeiro, Bahia, 693 serum samples of goat were collected from 46 farms from different locations in eight counties that make up this region (Campo Alegre de Lourdes, Casa Nova, Curaçá, Juazeiro, Pilão Arcado, Remanso, Sento Sé and Sobradinho). The samples were tested by agar gel immunodifusion (AGID) and the seroprevalence obtained was 0.87% (6/693). The low prevalence obtained was due to production features. The predominant system is the extensive one, with a presence of native, crossbred and mongrel animals, aiming at the production of meat and skin, with low productivity and technification.